Zmienność przepływów pieniężnych jako miara ryzyka produkcji energii z węgla brunatnego = Volatility of cash flows as a risk measure of electric energy production out of lignite - Jurdziak, Leszek; Woźniak, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper consists of four parts containing introduction, description of research methodology, analysis of results and conclusions. Main idea is the necessity of joint activity optimization of a lignite mine and a power station and working out the methodology of benefits of vertical integration estimation in conditions of uncertainty and risk in integrated software environment.
Keywords: węgiel brunatny; produkcja energii elektrycznej; ryzyko; lignite deposits; electric energy production; risk